Stroke services in the Middle East and adjacent region: A survey of 34 hospital-based stroke services - Al Hashmi, Amal. M.; Shuaib, Ashfaq; Imam, Yahia; Amr, Dareen; Humaidan, Hani; Al Nidawi, Firas; Sarhan, Ahmed; Mustafa, Wessam; Khalefa, Wael; Ramadan, Ismail; Usman, Fritz Sumantri; Hokmabadi, Elyar Sadeghi; et al. (Frontiers in Neurology, 2022)
Background: Acute stroke care is complex and requires multidisciplinary networking. There is insufficient data on stroke care in the Middle East and adjacent regions in Asia and Africa. Objective: Evaluate the state of readiness of stroke programs in the Middle East North Africa and surrounding regions (MENA+) to treat acute stroke. Method: Online questionnaire survey on the evaluation of stroke care across hospitals in the MENA+ region between April 2021 and January 2022. Results: The survey was completed by 34/50 (68%) hospitals. The median population serviced by participating hospitals was 2 million. The median admission of stroke patients/year was 600 (250 - 1100). The median length of stay at the stroke units was 5 days. 34/34(100%) of these hospitals have 24/7 CT head available. 17/34 (50%) have emergency guidelines for prehospital acute stroke care. Mechanical thrombectomy with/without IVT was available in 24/34 (70.6%). 51% was the median (IQR; 15 – 75%) of patients treated with IVT within 60 minutes from arrival. 35 minutes was the median time to reverse warfarin-associated ICH. Conclusion: This is the first large study on the availability of resources for the management of acute stroke in the MENA+ region. We noted the disparity in stroke care between high-income and low-income countries. Concerted efforts are required to improve stroke care in low-income countries. Accreditation of stroke programs in the region will be helpful.